Families and Intimate Relationships during COVID-19: Family Networks of Neapolitan Students - Fraudatario, Maria Camilla; Zaccaria, Riccardo (Italian Sociological Review, 2020)
Coronavirus pandemic immediately has taken on a global nature, transcending any national border, and unfolding its dramatic effects on every sphere of society: from health to economy, from politics to social relations. The lockdown of States and Regions has obligated everyone to isolation for long months, abruptly putting a stop to several social practices that were finding expression in daily physical places: working activities, education, leisure time, and cultural expressions. Many common efforts were directed to reorganise all these social and productive practices under quarantined time, growing the risk to degenerate on a temporal extension of daily life, and social-space dimension shrinking. This essay is focused on analysing how lockdown is affecting the daily life of families. Starting from a survey on families of students at University of Naples Federico II, it aims to reflect on family network’ dynamics pre and during lockdown.